Deep sequencing analysis of variants resistant to the non‐structural 5A inhibitor daclatasvir in patients with genotype 1b hepatitis C virus infection. Issue 14 (10th April 2014) - Miura, Mika; Maekawa, Shinya; Sato, Mitsuaki; Komatsu, Nobutoshi; Tatsumi, Akihisa; Takano, Shinichi; Amemiya, Fumitake; Nakayama, Yasuhiro; Inoue, Taisuke; Sakamoto, Minoru; Enomoto, Nobuyuki
<x xml:space="preserve">Abstract</x> Aim Daclatasvir, a non‐structural (NS)5A replication complex inhibitor, is a potent and promising direct antiviral agent (DAA) for hepatitis C virus (HCV), being most effective in genotype 1b infection. Although it is known that genotype 1b viruses with Y93H and/or L31M/V/F mutations have strong resistance to daclatasvir, it is not known whether there are some clinical background conditions that favor the occurrence of HCV carrying those NS5A mutations. Methods In this study, we carried out deep sequencing analysis of stored sera to determine the presence and significance of daclatasvir‐resistant mutants in 110 genotype 1b HCV‐infected patients with no previous daclatasvir treatment. Results Deep sequencing analysis revealed that the NS5A L31M/V/F and Y93H mutations were present in 13 (11.8%) and 34 (30.9%) of the 110 patients, respectively, and significantly more frequently than in the control plasmid. Simultaneous L31M/V/F and Y93H mutations were detected in four of the 110 patients (3.6%). When the clinical relevance of NS5A resistance was investigated, Y93H was significantly correlated with the IL28B major (TT) genotype of the host (P = 0.042). Conclusion Y93H was detected frequently by deep sequencing in daclatasvir treatment‐naïve patients. Importantly, it seems that the IL28B status of the patients may influence the presence of Y93H mutations, resulting in different treatment responses to daclatasvir.